Pemberdayaan Karangtaruna melalui Pelatihan Pembuatan Merchandise Berbasis Budaya Lokal - Eta Yuni Lestari; Slamet Sumarto; Puji Lestari; Nugraheni Arumsari (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to empower the youth organization (Karangtaruna) in Lau Village, Kudus Regency, through training on the production of local culture-based merchandise as an effort to preserve socio-cultural values and strengthen the local creative economy. The program adopted a community-based empowerment approach that emphasized the active participation of community members from the planning stage to evaluation. Sixteen youth members participated in various activities, including cultural conservation awareness sessions, participatory design and production training, digital marketing mentoring, and reflective discussions on sustainability. The results indicate significant improvement in participants’ awareness of cultural preservation, creative and entrepreneurial skills, and the emergence of local leaders who initiated collective business activities. The program successfully transformed the youth group from a passive community into an active, innovative, and self-reliant organization. At the national level, the activity supports the development of conservation-oriented character in line with the vision of Universitas Negeri Semarang as a conservation-minded university. At the global level, this initiative contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 11 (Sustainable Cities and Communities), by promoting youth participation as agents of change and reinforcing cultural sustainability within global development frameworks.